PERTIMBANGAN HAKIM TERHADAP TINDAK PIDANA PENYEBARAN DAN PELECEHAN BERBASIS TEKNOLOGI ELEKTRONIK (STUDI PUTUSAN NOMOR : 452/PID.SUS/2022/PN TJK) - syah, bagas muzekki; ramadan, suta (Qistie Jurnal Ilmu Hukum, 2023)
Abstract The current rampant cases of fading are really concerning especially with the development of technology which also affects the ease of spreading information which is then misused to spread things that are not good or aim to threaten and pressure victims by spreading content that is not good related to victims, the goal is that to find out the factors that caused the Defendant to commit the crime of spreading and harassment based on electronic technology and to find out the basis for the judge's considerations in imposing a criminal decision in the case of the crime of spreading and harassment based on electronic technology. The research method used is normative legal research. The legal materials used are sourced from the library. The types of legal materials used are primary, secondary and tertiary legal materials. The technique for collecting legal materials is by studying documents. Analysis of legal materials using interpretation or arrest. The results of the research show that the Crime of Technology-Based Dissemination and Harassment has been regulated in Article 27 Paragraph 1 of the ITE Law that Every Person intentionally and without rights distributes and/or transmits and/or makes Electronic Information and/or Electronic Documents that have contents that contain against decency. Keywords : Criminal Law, Harassment, Electronic Technology.